Pemeriksaan Resiko Cedera Pada Anggota UKORDA Unversitas Muhammadiyah Sidoarjo - Bagas Anjasmara; Andi Fadhilah Tenriwulan (jurnal ABDIMAS Indonesia, 2024)
Sports injuries are all forms of abnormalities and damages that occur in the body, both in the structure and function of the body that cause pain, resulting from physical movement and sports activities. This activity aims to determine the risk of sports injuries in athletes of UKM Sports Universitas Muhammadiyah Sidoarjo (UKORDA) by using Functional Movement Screening (FMS). UKORDA athletes as participants performed seven movements from the FMS examination consisting of movements consisting of (1) Deep Squat, (2) Hurdle Step, (3) In-Line Lunge, (4) Shoulder Mobility, (5) Active Straight Leg Raise, (6) Truck Stability Push Up, (7) Rotary Stability.The FMS assessment is given based on the effectiveness of the movements carried out by the sample, where the subject will be given a score of "0" if the subject fails or has pain when performing the movement. Then the subject is given a value of "3" if the movement performed is perfect. The results of the examination showed that 6 members of UKORDA were identified as having a "very high" risk of injury based on the results of the Functional Movement Screening (FMS) test, 10 people were identified as having "moderate-high" injury potential, while 9 other people were in the "moderate-low" category.